Temporary Blocking Internet Access on Papuan’s People: An Analysis of Article XIX on ICCPR in Handling Hoaxes - Khalil Armi; Sophia Listriani (Fakultas Hukum Universitas Syiah Kuala, 2021)
This study aims to analyze human rights violation on action that done by Indonesian government. The method used in this research is normative legal research. The results of this study shows that temporary blocked the internet to Papuan people is regulated under ICCPR and Indonesian law number 19 of 2016 about information and electronic transaction. Although, the reason for the temporary blocking action is to keep security of public but in other way that action was done in wrong procedure that make this action is illegal and against Indonesian law particularly law number 19 of 2016 about information and electronic transaction and also article 19 of international covenant on civil and political rights that have been ratified by Indonesian government through law number 12 of 2005 about ratification of ICCPR.Keyword : ICCPR, International Human rights, Freedom of Expression, Legal problems.